“Passorong Tedong” As A Requirement For The Validity Of Marriage According To The Tuho Law In Ulumanda District Majene Regency - Ika Novitasari (Journal of Scientific Research, Education, and Technology (JSRET), 2022)
Marriage is defined as a very strong contract or miistaaqan gholiidhan to obey God's commands and its implementation is a form of worship. In Islamic law, marriage is considered valid if the pillars and conditions of a valid marriage are met. These two elements are very basic and cannot be abandoned. However, in the Ulumanda District, the community imposes conditions other than those specified by the Shari'a and the Islamic Law Compilation. The condition is "Passorong Tedong", which determines the validity of a marriage in the Ada' Tuho community in Ulumanda District. This study discusses the conditions for the validity of marriage according to the Ada' Tuho Law and whether or not the application of these validity conditions is in line with the provisions of Islamic law. The results of the study show that the application of Massorong tedong as a condition for the validity of a marriage that is applied in the community in the Ulumanda District is contrary to the provisions of Islamic law, because this is not in accordance with the provisions regarding the legal requirements of a marriage that have been stipulated in the Marriage Law and Compilation of Islamic Law.